2017
DOI: 10.1075/lab.16010.van
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and experimental-behavioral approaches to the study of intra-sentential code-switching

Abstract: A hallmark of bilingual language processing is intra-sentential code-switching. An emergent body of research seeks to understand the intricate neural and cognitive mechanisms that underlie this seemingly effortless skill. In this paper, we discuss electrophysiological and experimental-behavioral research approaches that have been used to study intra-sentential code-switching, and illustrate the use of these techniques by discussing a select number of empirical studies. More specifically, we discuss electrophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 70 publications
2
26
0
Order By: Relevance
“…Within the study of bilingualism, there are also methodological concerns that pertain specifically to CS. In addition to merely defining the phenomenon, there are a plethora of other issues, including the merits of naturalistic and elicited CS data (MacSwan and McAlister 2010), attitudes toward CS ), CS grammaticality judgment task design (Stadthagen-González et al 2018), and experimental-behavioral techniques regarding CS comprehension and production (van Hell et al 2018), to name a few. Researchers such as Gullberg et al (2009) and González-Vilbazo et al (2013) also provide broader overviews, with the latter highlighting three prominent categories when it comes to methodological issues in CS research: project design, experimental procedure, and participant selection.…”
Section: Methods In Code-switching Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the study of bilingualism, there are also methodological concerns that pertain specifically to CS. In addition to merely defining the phenomenon, there are a plethora of other issues, including the merits of naturalistic and elicited CS data (MacSwan and McAlister 2010), attitudes toward CS ), CS grammaticality judgment task design (Stadthagen-González et al 2018), and experimental-behavioral techniques regarding CS comprehension and production (van Hell et al 2018), to name a few. Researchers such as Gullberg et al (2009) and González-Vilbazo et al (2013) also provide broader overviews, with the latter highlighting three prominent categories when it comes to methodological issues in CS research: project design, experimental procedure, and participant selection.…”
Section: Methods In Code-switching Researchmentioning
confidence: 99%
“…In (3b), the switch occurs within the verb phrase, where the auxiliary verb have is in English and its complement, the past participle, is in Spanish. Although there is debate surrounding the availability of auxiliary verb switches more generally as some have argued that they are all restricted (Belazi et al 1994;Timm 1975), whereas others suggest that progressive-tense switches can and do occur at the auxiliary-participle boundary (Bentahila and Davies 1983;Giancaspro 2015;Guzzardo Tamargo and Dussias 2013;Woolford 1983). Importantly these authors do not disagree when it comes to evidence against switching have/haber in Spanish-English mixed present-perfect sentences.…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been a common practice in studies examining the processing of codeswitched language to recruit bilingual speakers without examining their codeswitching background (e.g., Altarriba et al 1996;Hernandez et al 2001) and to employ experimental stimuli that contain switches that do not necessarily form part of the linguistic repertoire of the bilinguals being tested (for reviews, see Van Hell et al 2015Hell et al , 2018. To illustrate, in an eye-tracking study, Altarriba et al (1996) reported that first fixation durations were longer for high frequency Spanish words in semantically constraining English sentences compared to their English counterparts (5).…”
Section: Experimental Contributions Of Eye-tracking and Event-relatedmentioning
confidence: 99%
“…These different types of CS are not treated equally by linguists in terms of their theoretical importance and social significance. For example, intrasentential CS is considered to be a hallmark of bilingual language processing and studies of intrasentential CS can contribute to the understanding of neurocognitive mechanism involved in the language switching process (Van Hell, Fernandez, Kootstra, Litcofsky, & Ting, 2018;Van Hell, Litcofsky, & Ting, 2015). Marked and unmarked CS can index different sets of rights and obligations perceived by conversation participants (Myers-Scotton, 1993).…”
Section: Introductionmentioning
confidence: 99%